Relationship between oxidative balance score and post-stroke depression: insights from the NHANES 2005–2018 cross-sectional study - Li, Hai-Jun; Gao, Bo; Yan, Li-Ming; Xue, Yi-Dong; Wang, Tao (Frontiers in Neurology, 2024)
IntroductionThe Oxidative Balance Score (OBS) represents an integrated measure of oxidative-reductive homeostasis. Despite the established role of oxidative stress in the development of post-stroke depression (PSD), the association between OBS and PSD in the general population remains unclear. This study aims to explore this relationship using data from the National Health and Nutrition Examination Survey (NHANES) spanning 2005–2018.MethodsThe OBS was calculated using validated methods that incorporate dietary and lifestyle factors, whereas PSD status was determined using self-reported data and the Patient Health Questionnaire-9 (PHQ-9) scores. Multivariable logistic regression was employed to evaluate the associations of total OBS, dietary OBS, and lifestyle OBS with PSD prevalence, adjusting for potential confounders. Dose–response relationships were further assessed using restricted cubic splines (RCS).ResultsAmong the 26,668 participants included in the analysis, 201 were diagnosed with PSD. After adjusting for confounding variables, higher total OBS, dietary OBS, and lifestyle OBS were each significantly associated with reduced odds of PSD. The adjusted odds ratios (OR) and 95% confidence intervals (CI) for the highest versus lowest quartiles were 0.31 (95% CI: 0.15–0.67) for total OBS, 0.45 (0.27–0.73) for dietary OBS, and 0.28 (0.13–0.60) for lifestyle OBS. RCS analyses indicated a linear dose–response relationship for all three OBS categories with PSD risk. In sex-stratified analyses, significant inverse associations were observed between all OBS categories and PSD in females, whereas only lifestyle OBS was significantly associated with PSD in males.ConclusionHigher OBS was associated with reduced odds of PSD, with a particularly pronounced effect in females. These findings suggest that adherence to an antioxidant-rich diet and lifestyle may mitigate PSD risk.